ANTIBACERIAL ACTIVITY OF ENDOPHYTIC FUNGI ISOLATE OF PAINTED NETTLE (Coleus scutellarioides L. Benth.) AGAINST SKIN INFECTION BACTERIA USING TLC-BIOAUTOGRAPH AND AGAR DIFFUSION METHODS - Bonita S, Elivilia Oktaviana (Journal Microbiology Science, 2022)
Painted Nettle (Coleus scutellarioides L. Benth.) has properties as anti-inflammatory, antioxidant, and antibacterial. It accelerates wound healing as well. Painted nettle contains essential oils, phenols, tannins, phytosterols, alkaloids, and flavonoids. This study aimed to obtain endophytic fungi isolates that have the potential as antibacterial by TLC-Bioautography and agar diffusion methods. This research was conducted by isolating endophytic fungi of painted nettle, advanced to purification and macroscopic tests and nine pure isolates were obtained. The results of the isolate screening with the IFDI code 6 showed the highest inhibition. Furthermore, the antibacterial activity was assayed by TLC-Bioautography. The results obtained two active spots (Rf1 = 0.96; Rf2 = 0.25) against Staphylococcus aureus and Staphylococcus epidemics, three active spots (Rf1 = 0.96; Rf2 = 0.61; Rf3 = 0.25) against Psedudomonas aeruginosa. The results of the antibacterial activity assay by diffusion method obtained inhibitory zone for each bacterium, namely Staphylococcus aureus at 8.95 mm, Staphylococcus epidermidis at 8.24 mm, and Pseudomonas aeruginosa at 7.46 mm.Key words: Antibacterial, agar diffusion, endophytic fungi, skin infections, TLC Bioautography